When Confidence Breeds Contempt: Exploring the Link Between Self-Esteem and Schadenfreude in Students - Subhan Ajrin Sudirman; Indah Andika Octavia; Suci Anggraini Gusni Aulia (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the problems that arise due to the competitive campus climate so that students often make social comparisons that trigger jealous behavior, unhealthy competition, and feelings of joy over the failure of others that indicate schadenfreude actions. One of the factors that influences schadenfreude is self-esteem. The purpose of this study was to determine whether there is an effect of self-esteem on schadenfreude in students. This study uses a quantitative approach with a simple linear regression analysis test. Sampling in this study used the Slovin formula with a 0.5% error rate of 385 students. The sampling technique used was a random technique by dividing the distribution of subjects in each faculty using proportionate stratified random sampling. The data collection technique was carried out by distributing the self-esteem scale and the schadenfreude scale using the Likert model. The level of self-esteem categorization is in the moderate category with a percentage of 49.6% and the schadenfreude categorization is in the moderate category with a percentage of 55.6%. The results of this study indicate that self-esteem has a significant effect on schadenfreude with a contribution percentage of 17.5% which refers to a significance value of 0.000 (p <0.05) with a negative influence direction based on the unstandardized coefficient value of -0.462. This confirms that self-esteem has an important role in reducing feelings of joy over other people's failures.